Knowledge, awareness and practices related to Hepatitis-B infection and vaccine among general population in Chengalpattu, Tamil Nadu - Abdullah, Zoha; Prathiyumannan, Priya; Mani, Rajameena; Marimuthu, Rajanila; Rasheed, Rashmina; Patil, Rohit Chandrakanth; Mariappan, Roshini; Premnath, Parvathy (International Journal Of Community Medicine And Public Health, 2021)
Background: In India, 1,50,000 deaths are reported annually and 60 million people are affected due to Hepatitis B virus. For any government prevention programs to succeed, community awareness and participation is vital. Therefore, this study sought to assess the knowledge and awareness of hepatitis-B virus and vaccination among general population in rural areas. We also assessed the practices related to the hepatitis B vaccination. Methods: We conducted a house to house survey in villages of Chengalpattu district. A total of 323 participants agreed to participate in the survey. A 22 item questionnaire was administered to assess the knowledge, awareness and practice. Data were entered in Microsoft Excel spreadsheet and analyzed using Statistical package for social sciences (SPSS) software. Independent t test was used to assess the difference in responses based on the independent variables. Pearson’s correlation was used to analyze the association between the level of knowledge, awareness and practice scores. Results: A total of 323 participants agreed to participate in the survey. Nearly, 87.9% had never heard about hepatitis B. The awareness of a vaccine for hepatitis B among the study subjects was 6.5%. Higher knowledge, awareness and practice were found among those with higher education and working professionals (p<0.05). Knowledge, awareness and practice were positively correlated (p<0.005). Conclusions: It can be concluded that the levels of knowledge, awareness and practice in the rural population of Chengalpattu district, Tamil Nadu were marginally low. Extensive awareness and prevention programs related to Hepatitis B virus and its vaccine should be conducted targeting high risk populations.